South Korea Strategy in Increasing Exports of Beauty Products to Indonesia in Covid-19 Pandemic - Fadhilah, Reidhati Dayang; Jatmika, Sidik (Green Publisher Indonesia, 2022)
The Covid-19 pandemic has hampered the economic growth of countries in the world. Many industries were unable to survive the crisis that occurred as a result of the pandemic. However, this does not apply to the South Korean cosmetic industry or K-Beauty. During the pandemic, sales of K-Beauty in the world actually increased. This study aims to determine and analyze South Korea's strategy in increasing exports of beauty products (K-Beauty) to Indonesia during the Covid-19 pandemic (2019-2021 years). This research is descriptive research. The data collection method used was library research. The results showed that during the Covid-19 pandemic, South Korea continued to use the Korean Wave/Hallyu as a strategy in increasing exports of beauty products (K-Beauty) to Indonesia (2019-2021) as evidenced by the many policies and support from the South Korean Government to continue developing Korean Wave/Hallyu in Indonesia. In addition, the push to accelerate IK-CEPA is also used as a strategy to increase exports of beauty products (K-Beauty) to Indonesia.